The meaning of suffering in patients with advanced progressive cancer. (September 2015) - Ellis, Jackie; Cobb, Mark; O'Connor, Tina; Dunn, Laurie; Irving, Greg; Lloyd-Williams, Mari
Background: There is a lack of research into suffering and what it means to the individual patient with advanced cancer and its importance in end of life care. Aims: To explore the concept of suffering and distress by eliciting what individual patients with advanced cancer perceived as suffering and how they utilised their own resources to manage suffering. Method: A qualitative study design of focused narrative interviews analysed by thematic analysis was conducted with a heterogeneous sample of 49 palliative day care patients. Results: For those patients who perceived they were suffering, this study revealed a wide spectrum of definitions which could be described within the following areas; the unavoidable and avoidable suffering, physical and emotional suffering, suffering as loss and finally transformation through suffering. Conclusions: These findings provide important insight that broadens and enriches our understanding into the concept of suffering and how patients utilise their resources, which may have important implications for end of life care.